If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3y + 1 = 8 Reorder the terms: 1 + -3y = 8 Solving 1 + -3y = 8 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1' to each side of the equation. 1 + -1 + -3y = 8 + -1 Combine like terms: 1 + -1 = 0 0 + -3y = 8 + -1 -3y = 8 + -1 Combine like terms: 8 + -1 = 7 -3y = 7 Divide each side by '-3'. y = -2.333333333 Simplifying y = -2.333333333
| 4(y+2)= | | 3.5*5= | | -3v+15=0 | | 5(14+x)= | | (-4x+33)=(2x+81) | | 6v+13= | | C=9/210+12 | | xsquared=2x | | p-31p= | | 5(1+6)= | | 36-12x=6(x+12) | | -1=-6x+13 | | (6x+14)=(3x+29) | | 24s/3s | | x+8=0+2x | | 2u-5=-3 | | 2(x+5)+3(x-7)=9 | | 3w+2/=-12 | | 17=-8w-15 | | 2=26-4x | | 9(2x+2)=22x | | (y+4/3)-(y-4/25)=1 | | -0.5u+2.5=3.5 | | -3(2s-2)-6=-2(9s+1)-3 | | y^4+8y^3+15y^2= | | 9x+18x-27=6x-9x+9 | | 0.18(24)+0.03x=0.06(24+x) | | xy-2a+ay=0 | | 0.20(6)+0.05x=0.10(6+x) | | -11=4v+10 | | 0=-16t^2+48t+5 | | M^2+7m=30 |